2015
DOI: 10.3311/pptr.7742
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Contributing to Taxi Involved Crashes: A Case Study in Xi’an, China

Abstract: Using the 612 valid samples deriving from the original 6259 crash reports in Xi'an from 2006 to 2011, comparative statistics and systematic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In Britain, 31% of fatal crashes and 26% of serious injury crashes involve occupational drivers [18]. A survey in Xi'an, China revealed that the average number of taxi crashes per month was 8.500 over the period of 2006 to 2011 [4]. Our previous study also showed that 47.34% of the occupational bus, taxi, lorry, company car and shuttle drivers in Xining, China had caused crashes at some point [19].…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Britain, 31% of fatal crashes and 26% of serious injury crashes involve occupational drivers [18]. A survey in Xi'an, China revealed that the average number of taxi crashes per month was 8.500 over the period of 2006 to 2011 [4]. Our previous study also showed that 47.34% of the occupational bus, taxi, lorry, company car and shuttle drivers in Xining, China had caused crashes at some point [19].…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Many studies have been conducted to examine the significant effect of exposure to hazardous working conditions on taxi drivers' health and to identify potential risk factors contributing to road crashes, such as drivers' age, job experience [4], license, type of employment [5], and physical and mental health [3,6,7]. Generally, taxi drivers are regularly obliged to work long hours into the late night or early morning and are therefore vulnerable to fatigue or sleepiness while driving [3,4,8,9]. Moreover, occupational illness [10], irregular shifts [3], and income dissatisfaction [11] have also been significantly correlated with taxi drivers' risk of serious crashes.…”
Section: Introductionmentioning
confidence: 99%
“…Taxis have recently taken on a considerable share of the transport market in China, because of their comfort, convenience and flexibility. Previous studies have focused on the safety records of taxi drivers [46][47][48], and on atmospheric pollutants in taxi cabins. For the taxi, just as for the private car, ventilation settings have been shown to have a significant impact on in-vehicle mass and number concentrations [39,49].…”
Section: Taximentioning
confidence: 99%
“…Zhao et al (2015) noticed that for Xi'an city the taxi drivers with 3 to 5 years experience are at greater risk for crashes than other groups. The results of the present study corroborate with those found in Xi'an city.…”
Section: Fig 2 Steps Acquisition and Transmission Of Informationmentioning
confidence: 99%